Aprendizagem musical na prática coral: estudo de um coro sacro da cidade de Ouro Preto-MG - Luan Carlos Oliveira (2023)
This research aimed to investigate how the musical learning of the choir members of Coral São Pio X takes place, a sacred choir founded in 1959 in the historic city of Ouro Preto-MG. It is a choir that adopts a repertoire composed, in large part, of colonial sacred music and that has a great performance in the city's traditional religious festivities. The choir is made up of amateur singers and there is no formal structure for teaching music. The investigation used mixed method data collection techniques, collecting quantitative data through instruction and qualitative data through participant observation and semi-structured interviews. The methodological approach, however, was predominantly qualitative. The theoretical foundation sought support in the learning theories of Knud Illeris (2007, 2013) and Etienne Wenger (1998, 2013) which provided parameters for the development of analyzes on the learning processes in dialogue with authors in the areas of Music Education and Choral Singing (DIAS 2011; FIGUEIREDO, 1990; FIGUEIREDO, 2010; FUCCI AMATO, 2007; OLIVEIRA, 2011; SILVA, 2017; SWANWICK, 2003). For the discussion of the data we used the categories that emerged from the adopted theories, being the "learning dimensions" of Illeris's theory: content, incentive and interaction and the "components of the Social Theory of Learning" of Wenger: meaning, practice, community and identity. The results reflect the emotion of the emotional and motivational aspects of learning, as well as the sharing of knowledge, the helping relationships between the members and the conductor's action as a mediator of musical knowledge in the choir.